Critical care outreach community program for primary care nurses and the outcome to critical illness survivors - Mohamed Ludin, Salizar; Mat Nor, Mohd Basri; Muthu, Matron Devi Saravana (2016)
INTRODUCTION: Critical illness survivors have reported problems and many of them had serious life-threatening illnesses and experience multiple challenges to their recovery. In particular the alterations in physical function or debilitating effect of an illness itself and these changes the overall functional capacity. Due to that, Critical Care Outreach services (CCOS) has been introduced long time ago in the UK, and Australia to provide knowledge and care to survivors to prevent impairment and assisting survivors to smooth rehabilitation.The Community nurses are the most important people that should be providing CCOS however to date, CCOS is not available in Malaysia and the community nurses’ knowledge attitude and skills on CCOS are presumably inadequate.